2009
DOI: 10.2166/nh.2009.001
|View full text |Cite
|
Sign up to set email alerts
|

Imputation of missing values in a precipitation–runoff process database

Abstract: Hydrologists are often faced with the problem of missing values in a precipitation–runoff process database to construct runoff prediction models. They tend to use simple and naive methods to deal with the problem of missing data. Thus far, the common practice has been to discard observations with missing values. In this paper, we present some statistically principled methods for gap filling and discuss the pros and cons of these methods. We employ and discuss imputations of missing values by means of self-orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(44 citation statements)
references
References 0 publications
0
44
0
Order By: Relevance
“…Previous studies [9,17,18] have reported as well that the self-organizing map (SOM), an unsupervised ANN, showed satisfactory imputation results. These nonlinear models have demonstrated their performances by showing better imputation results than the traditional statistical methods [19].…”
Section: Introductionmentioning
confidence: 96%
“…Previous studies [9,17,18] have reported as well that the self-organizing map (SOM), an unsupervised ANN, showed satisfactory imputation results. These nonlinear models have demonstrated their performances by showing better imputation results than the traditional statistical methods [19].…”
Section: Introductionmentioning
confidence: 96%
“…The process repeats in this way until all the missing entries of b are imputed. Variants of this method are considered in [86], [143], and [281].…”
Section: Best Neighbor Imputingmentioning
confidence: 99%
“…Next, the SOM will search the best matching unit (BMU) by computing the Euclidean distance to the input vector. (2) where W is weight vector. The determination of the node that are within the BMU`s neighbourhood is made by calculating the radius of the neighbourhood, σ(t) and it will decrease over time as…”
Section: Basic Of Self-organizing Mapmentioning
confidence: 99%
“…Kalteh and Hjorth (2009) used SOM to construct a complete database of runoff prediction in Northern Iran. Multiple imputation, multivariate nearest neighbour, multilayer perceptron (MLP) and means of SOM are the imputation methods used to estimate the missing data.…”
Section: Introductionmentioning
confidence: 99%